Biochemical and Genetic Analysis of 4-Hydroxypyridine Catabolism in Arthrobacter sp. Strain IN13 - Justas Vaitekūnas; Renata Gasparavičiūtė; Jonita Stankevičiūtė; Gintaras Urbelis; Rolandas Meškys (Microorganisms, 2020)
N-Heterocyclic compounds are widely spread in the biosphere, being constituents of alkaloids, cofactors, allelochemicals, and artificial substances. However, the fate of such compounds including a catabolism of hydroxylated pyridines is not yet fully understood. Arthrobacter sp. IN13 is capable of using 4-hydroxypyridine as a sole source of carbon and energy. Three substrate-inducible proteins were detected by comparing protein expression profiles, and peptide mass fingerprinting was performed using MS/MS. After partial sequencing of the genome, we were able to locate genes encoding 4-hydroxypyridine-inducible proteins and identify the kpi gene cluster consisting of 16 open reading frames. The recombinant expression of genes from this locus in Escherichia coli and Rhodococcus erytropolis SQ1 allowed an elucidation of the biochemical functions of the proteins. We report that in Arthrobacter sp. IN13, the initial hydroxylation of 4-hydroxypyridine is catalyzed by a flavin-dependent monooxygenase (KpiA). A product of the monooxygenase reaction is identified as 3,4-dihydroxypyridine, and a subsequent oxidative opening of the ring is performed by a hypothetical amidohydrolase (KpiC). The 3-(N-formyl)-formiminopyruvate formed in this reaction is further converted by KpiB hydrolase to 3-formylpyruvate. Thus, the degradation of 4-hydroxypyridine in Arthrobacter sp. IN13 was analyzed at genetic and biochemical levels, elucidating this catabolic pathway.